Caribbean sexuality : a pastoral counsellor looks at family patterns and the influences of culture on Caribbean people - Waithe, Neilson A. (Moravian Church in America BethlemUS, 1993)
Explains those influences and factors which impact on and shape the sexuality of Caribbean people.